Prevalence and Predictors of Silent Gastroesophageal Reflux Disease in Patients with Hypertension - He Suyu; Yijun Liu; Xu Jianyu; Guiquan Luo; Lipeng Cao; Xiaoqi Long (Gastroenterology Research and Practice)
Background. Gastroesophageal reflux disease (GERD) without symptoms or silent GERD can be easily missed in patients with hypertension. We aimed to investigate the prevalence of GERD, specifically the prevalence of silent GERD in hypertensive patients, and to explore its possible predictors. Methods. Consecutive patients with hypertension referred to the cardiovascular clinic of Suining Central Hospital in 2016 were screened for this study. A Reflux Disease Questionnaire (RDQ) and an esophagogastroduodenoscopy (EGD) were employed for the evaluation of silent GERD. Included patients were divided into silent-GERD group and non-GERD control group. The demographic characteristics and antihypertensive agent prescriptions were collected and compared between the two groups. Results. The prevalence of silent GERD and GERD in patients with hypertension was 15.1% and 31.4%, respectively. 66 patients were included in the silent-GERD group, and 298 patients were included in the non-GERD control group. Abdominal obesity and untreated hypertension were positive predictors, while controlled hypertension was a negative predictor for silent GERD. The prescription of calcium channel blockers was not a predictor for it. Conclusions. High prevalence of GERD, specifically silent GERD, could be found in patients with hypertension. Abdominal obesity and untreated hypertension were positive predictors for silent GERD, while controlled hypertension was a negative predictor for it.